2020
DOI: 10.1093/erae/jbaa014
|View full text |Cite
|
Sign up to set email alerts
|

The optimal drought index for designing weather index insurance

Abstract: Climate change increases the need for better insurance solutions that enable farmers to cope with drought risks. We design weather index insurance using drought indices based on precipitation, soil moisture and evapotranspiration as underlying drought index and compare their risk-reducing potential for winter wheat producers in Eastern Germany. In general, we find that all drought indices can reduce financial risk exposure. However, the largest risk reduction can be achieved if the underlying drought index is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 83 publications
0
33
0
Order By: Relevance
“…OLS is not the only commonly used method for estimating trends. For instance, some authors have reported that the Theil‐Sen, M and MM estimators are more robust to outliers (Finger, 2013), and quantile regression can be used to estimate the median and other quantiles (Bucheli et al, 2020; Conradt et al, 2015; Dalhaus et al, 2018). However, these methods are more difficult to include in model averaging frameworks, which is the main focus of this study.…”
Section: Data Ols Trends and Statistical Significancementioning
confidence: 99%
“…OLS is not the only commonly used method for estimating trends. For instance, some authors have reported that the Theil‐Sen, M and MM estimators are more robust to outliers (Finger, 2013), and quantile regression can be used to estimate the median and other quantiles (Bucheli et al, 2020; Conradt et al, 2015; Dalhaus et al, 2018). However, these methods are more difficult to include in model averaging frameworks, which is the main focus of this study.…”
Section: Data Ols Trends and Statistical Significancementioning
confidence: 99%
“…New insurance options, such as for example insurance schemes based on satellite imagery, can contribute to increasing the resilience of European farming systems to extreme weather risks, in both crop and livestock production. Drawing on findings from the SURE‐Farm project, this article provides an overview of recent developments in agricultural insurance research (Bucheli et al ., 2020; Vroege et al ., 2019; Vroege et al ., 2020a; Vroege et al ., 2020b).…”
Section: Weather Risk Management In Agriculturementioning
confidence: 99%
“…As a result, there are still few drought insurance options available to farmers – even though drought is an important and increasing risk for European agriculture. We thus aimed to provide insights on how differently an optimal drought insurance contract could be designed (Bucheli et al ., 2020). In this contribution, we specifically address two questions.…”
Section: Sure‐farm Contributionsmentioning
confidence: 99%
“…In reality, the timing of a crop's sensitivity to weather may vary significantly across fields due to differences in management practices, such as variety and sowing dates, as well as meteorological conditions, which affect rates of crop development [15]. Failure to consider this heterogeneity may lead to inaccurate estimation of yield losses and basis risk [16,17].…”
Section: Introductionmentioning
confidence: 99%